(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the morphological and semantic representation system of the category of tense in Uzbek and English. The similarities and differences of tense forms in both languages are considered on the basis of a comparative approach. The study analyzes the functional loads of grammatical means, verb forms and time indicators in speech.